Establishment and characterization of a mouse tumor cell line with irreversible downregulation of MHC class I molecules - Lhotakova, Karolina; Grzelak, Adrianna; Polakova, Ingrid; Vackova, Julie; Smahel, Michal (Oncology reports, 2019)
In the majority of human tumors, downregulation of major histocompatibility complex class I (MHC‑I) expression contributes to the escape from the host immune system and resistance to immunotherapy. Relevant animal models are therefore needed to enhance the efficacy of cancer immunotherapy. As loss of β‑2 microglobulin expression results in irreversible downregulation of surface MHC‑I molecules in various human tumors, the β‑2 microglobulin gene (B2m) was deactivated in a mouse oncogenic TC‑1 cell line and a TC‑1/dB2m cell line that was negative for surface MHC‑I expression was derived. Following stimulation with interferon γ, MHC‑I heavy chains, particularly the H‑2Db molecules, were found to be expressed at low levels on the cell surface, but without β‑2 microglobulin. B2m deactivation in TC‑1/dB2m cells led to reduced proliferation and tumor growth. These cells were insensitive to DNA vaccination and only weakly responsive to combined immunotherapy with a DNA vaccine and the ODN1826 adjuvant. In vivo depletion demonstrated that NK1.1+ cells were involved in both reduced tumor growth and an antitumor effect of immunotherapy. The number of immune cells infiltrating TC‑1/dB2m‑induced tumors was comparable with that in tumors developing from TC‑1/A9 cells characterized by reversible MHC‑I downregulation. However, the composition of the cell infiltrate was different and, most importantly, infiltration with immune cells was not increased in TC‑1/dB2m tumors after immunotherapy. Therefore, the TC‑1/dB2m cell line represents a clinically relevant tumor model that may be used for enhancement of cancer immunotherapy.
Keywords: beta-2-mikroglobulin; Gene Expression Regulation, Neoplastic; Interferon-gamma; Neoplasms; Cell Line, Tumor; regulace genové exprese u nádorů; Histocompatibility Antigens Class I; T-Lymphocytes, Cytotoxic; interferon gama; MHC antigeny I. třídy; Immunotherapy; cytotoxické T-lymfocyty; Animals; lidé; Humans; zvířata; imunoterapie; myši; beta 2-Microglobulin; nádory; nádorové buněčné linie; Mice